Pengendalian Filamen Bubbling Dari Material Petg Pada Proses Cetak 3 Dimensi - Adam, Adam Ridho; Ramadhan, Ali (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Control is the measurement and improvement of an implementation so that the implementation is in accordance with the plans that have been made to achieve a goal. Bubbling is one of the failures in the 3d print printing process, this can happen because the filament is damp/contains a lot of moisture. Printing a 3D object requires precision because all aspects of preparation must be done properly so that the object being printed is successful. Well, in this study the authors used a case study type of research, the authors will conduct a description and analysis of the bubbling filament case. The analysis carried out is to analyze the factors that affect the PETG material filaments to become moist and analyze the appropriate PETG material storage methods so that the quality of the material remains optimal